Implementasi Model Demonstrasi dalam Meningkatkan Minat Belajar Siswa pada Mata Pelajaran SKI Kelas XI C MA Plus Sunan Kalijogo Pogalan Trenggalek Semester Genap Tahun Ajaran 2023/2024 - Choirul Anam; Uswatun Hasanah; Nasrul Fuad Erfansyah (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2025)
This classroom action research aims to increase students' interest in learning in class XIC MA Plus Sunan Kalijogo for the 2023/2024 academic year in the subject History of Islamic Culture (SKI) through demonstration learning methods. This research was conducted in class XIC, totaling 23 students, based on a lack of interest in learning SKI because students felt bored and sleepy. This classroom action research was divided into two cycles. Data collection takes the form of observations, interviews and written tests. The results of the research show that there is a development of students' interest in learning which is characterized by increased student activity in asking questions, stable student attendance, and increased grades. In cycle 1 the percentage of student attendance reached 96 percent, and in cycle 2 it reached 97 percent. Apart from that, the average student score also increased, in cycle 1 the average student score was 75,6, and in cycle 2 the average student score was 79,1. With the existing data, it can be concluded that the demonstration method can increase students' interest in learning SKI in class XIC MA Plus Sunan Kalijogo Pogalan Trenggalek.